A study on the Anatomical Variations in the Formation of Renal Pelvi-calyceal System in Population of Northeast India - Mousumee Saikia; Rajat Roy; Debabani Bora (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2023)
Background and aim: The renal pelvicalyceal system consists of the renal pelvis and the two groups of calyces - the major and the minor. Wide variations in the formation of this system have been reported earlier. The study aimed to provide a clear picture of the morphology as well as the anatomical variations associated with the human renal pelvicalyceal system in the Northeast Indian population that can help to minimize injuries and complications associated with various surgical and radiological interventions in this region.Material and methods: The study was conducted on 160 formalin-fixed specimens collected after dissection from adult and perinatal cadavers above 36 weeks of age. All the specimens were numbered accordingly, and piecemeal dissection was done.Results: The study showed a predominance of the intrarenal pelvis, with the bicalyceal arrangement of major calyces being more than the tricameral pattern. 89.37% of specimens showed normal patterns as described by standard textbooks and authors of previous studies. Meanwhile, 10.62% of specimens had unusual variations, mainly on the right side. These include the absent pelvis, bifid pelvis, absent major calyx, mega calyx, elongated superior calyx, thick major calyx, four major calyx, and dilated calyces. The most commonly occurring variation was absent major calyx (3.75%), followed by absent pelvis (2.5%) and megacalyx (2.3%).Conclusions: The study showed that the renal pelvicalyceal system exhibits various variations. Proper knowledge of these structures' normal and variant anatomy is the key to safe radiological and urological interventions.